Spontaneous mid-oesophageal rupture. Issue 634 (August 1978) - Holt, S.; Millar, J. W.; Heading, R. C.; Charles, R. G.
Abstract : The clinical presentation and management of spontaneous rupture of the middle third of the oesophagus is described in two patients. Early presentation and treatment in one case led to uncomplicated recovery. In the other patient late presentation and diagnosis resulted in delayed surgical intervention with an unsuccessful outcome. The nature of this rare lesion is discussed and nine previously described cases are reviewed.